Design And Develop Automatic Battery Cyclic Tester - Ramdan, Razali; Mortaza, Mohamed; Abdalla, Ahmed N.; Muhammad, Rauf (2013)
In EV and HEV, the power battery must capable of performing charge and discharge for longer period of time imply that longer life cycle of the battery. Hence, batteries are required to undergo cyclic battery test. However, the cyclic test is time consuming that will result in long waiting time for the test to complete. Chemical reaction in each battery are varies thus affecting the battery performance. Thus, the need for fully automated cyclic test station is appear. In this paper will focus on the design and development of automation of the battery cyclic tester. An analog output is used to send signal to the driver circuit and energizes relay that control charging and discharging s for each bat battery's charging switch of the battery. A PC based system for testing batteries in a fully controlled environment has to be developed. The system must able to perform fully-automated battery cyclic test. The result, as expected reduces man-hour waiting time during conducting battery testing. In addition of conventional battery cyclic test, it costs a great expense for battery manufacturers to verify battery life cycle. In addition, with this system all parameters involved in battery charging-discharging processes are obtained.